Julie Gouraud et Saint-Domingue : du roman familial au roman pour enfants - Michel Manson (Strenae)
Julie Gouraud's novel, The two children of St. Domingo, published in the "Bibliothèque Rose illustrée" in 1874, is carefully analyzed here to determine what arises from stereotypes of slavery, black people, and the plantation system in colonial children's literature, and what results from the story of the author's mother, a Creole who escaped as a child during the revolt of 1791. Archival documents and contemporary works on Saint-Domingue are used, and the novel is compared to other children's books about Saint-Domingue and its revolution. The result is a nuanced view of how one children's author blends her family novel with genre norms.